Study of other religions in light of AbdulHamid AbuSulayman’s notion of Islamisation of Knowledge (IoK) - Ibrahim, Haslina (International Institute for Muslim Unity (IIMU), IIUM, 2024)
This chapter discusses how the teachings of the study of other religions can be revived in the light of AbuSulayman’s notion of Islamization of Knowledge (IOK) to restore the purpose of knowledge seeking and its meaning in an Islamic intellectual endeavor. The author used the qualitative approach of thematic analysis in analyzing AbuSulayman’s ideas of IOK under three guiding themes which include: (1) the need for heritage and the traditional method, (2) the question of objectivity and impartiality of Truth, and (3) the Islamic methodology in studying other religions. In this chapter, the following issues are discussed: firstly, the diagnosis and the state of the art in the modern study of religions; secondly, AbuSulayman’s notion of IOK and Muslims intellectual awakening; thirdly, epistemological and ethical concerns in the modern study of religions; and fourthly, IOK and the study of religions at an Islamic institution.